Family matters: sibling rivalry and bonding between p53 and p63 in cancer. Issue 4 (16th March 2014) - Romano, Rose‐Anne; Sinha, Satrajit
Abstract The p53 family (p53, p63 and p73) is intimately linked with an overwhelming number of cellular processes during normal physiological as well as pathological conditions including cancer. The fact that these proteins are expressed in myriad isoforms, each with unique biochemical properties and distinct effects on tumorigenesis, complicates their study. A case in point is Squamous Cell Carcinoma (SCC) where p53 is often mutated and the ΔNp63 isoform is overexpressed. Given that p53 and p63 can hetero‐dimerize, bind to quite similar DNA elements and share common co‐factors, any alterations in their individual expression levels, activity and/or mutation can severely disrupt the family equilibrium. The burgeoning genomics data sets and new additions to the experimental toolbox are offering crucial insights into the complex role of the p53 family in SCC, but more mechanistic studies are needed.